Intelligent blind source separation technology based on OTFS modulation for LEO satellite communication - Li, Chengjie; Zhu, Lidong; Guo, Cheng; Liu, Tao; Zhang, Zhen (China communications, 2022)
In LEO (Low Earth Orbit) satellite communication system, the orbit height of the satellite is low, the transmission delay is short, the path loss is small, and the frequency multiplexing is more effective. However, it is an unavoidable technical problem of the significant Doppler effect caused by the interference between satellite networks and the high-speed movement of the satellite relative to the ground. In order to improve the target detection efficiency and system security of LEO satellite communication system, blind separation technology is an effective method to process the collision signals received by satellites. Because of the signal has good sparsity in Delay-Doppler domain, in order to improve the blind separation performance of LEO satellite communication system, orthogonal Time-Frequency space (OTFS) modulation is used to convert the sampled signal to Delay-Doppler domain. DBSCAN clustering algorithm is used to classify the sparse signal, so as to separate the original mixed signal. Finally, the simulation results show that the method has a good separation effect, and can significantly improve the detection efficiency of system targets and the security of LEO satellite communication system network.